ChemInform Abstract: Heterogeneous Catalytic Oxidation for Lignin Valorization into Valuable Chemicals: What Results? What Limitations? What Trends?. Issue 22 (12th May 2016) - Behling, R.; Valange, S.; Chatel, G.
Abstract: Review: 105 refs.